The Bereg flooding in 2001 – Impacts on the built environment - Kiss, Alida (Acta Agraria Debreceniensis, 2013)
Today, an increasing number of natural disaster events are witnessed. Our respond to these disasters is increasingly important and more timely problem. Before PhD studies my research aimed at revealing the impacts reconstruction, restoration and damage prevention had on the environmental, social and economic segments of disaster-hit areas. This present paper intends to provide preliminary results of the work already carried out in the Bereg Region, where I specialized on the effects of Tisza flood.This paper focuses on the results and conclusions drawn from the analysis of environmental consequences resultant from the flood based on a study area.